2020
DOI: 10.1177/1359104520962155
|View full text |Cite
|
Sign up to set email alerts
|

Attachment to parents and friends and body dissatisfaction in adolescents with eating disorders

Abstract: The study of attachment is a valuable theoretical framework to understand the influence of parents and friends on the evolution and development of adolescents. This study aimed to determine parents’ and peers’ attachment style, the relationship between parents’ and peers’ attachment and body dissatisfaction in adolescents with eating disorders (ED), and to compare it with a control group. The sample consisted of 260 adolescents ( Mage = 15.35, SDage = 1.461): a control group consisting of 129 non-clinical subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
4
10
0
Order By: Relevance
“…Our study suggests that for eating disorder psychopathology friendships to peers play a particularly important role. This is in line with Cunha et al [22] but contrasts the results of others [23,25] who found eating disorder psychopathology to be related more strongly to relationship quality to mothers and/or fathers than to relationship quality to peers.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Our study suggests that for eating disorder psychopathology friendships to peers play a particularly important role. This is in line with Cunha et al [22] but contrasts the results of others [23,25] who found eating disorder psychopathology to be related more strongly to relationship quality to mothers and/or fathers than to relationship quality to peers.…”
Section: Discussionsupporting
confidence: 87%
“…The groups differed not only in all three relationships but also on all subscales of relationship quality: adolescents with AN reported lower Trust, lower Communication, and higher Alienation in their relationships than healthy adolescents. In addition, relationship quality scores were negatively correlated with eating disorder symptoms (in line with [19,23,25]). Effect sizes for group differences were largest for relationships to peers and the correlation with eating disorder symptoms was significantly larger for relationships to peers than for relationships to parents, suggesting that peer relationships might be particularly impaired in adolescents with AN.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Family meals may promote a model of healthy eating behaviors and create a communication of cohesion, developing a healthier perception of self, and thus, accordingly to our approach, a better well-being perception [ 9 , 24 ]. On the contrary, negative family experiences that induce lower confidence are associated with an increase in eating disorders [ 25 ]. Another important result concerns the relationship between psychotropic drugs use and the well-being perception.…”
Section: Discussionmentioning
confidence: 99%